1983
DOI: 10.1088/0022-3700/16/8/012
|View full text |Cite
|
Sign up to set email alerts
|

Multiply charged ions induced by multiphoton absorption processes in rare-gas atoms at 1.064μm

Abstract: Multiply charged ions are easily formed in rare gases by multiphoton absorption processes. For Kr and Xe up to quadruply charged ions are formed. They are induced by a bandwidth-limited 50 ps laser pulse at 1.064 W cm-2 intensity range. Doubly charged ions are formed through the absorption of a very large number of photons (29 for Xe) in a direct transition from the ground state of the atom to the second ionisation limit. The percentage of Xe2+ ions relative to Xe+ ions is 1% at 1013 W cm-2, and reaches 20% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(66 citation statements)
references
References 17 publications
4
62
0
Order By: Relevance
“…Also, for a given power output, the peak intensity in short laser pulses is higher than in longer ones, and hence we should expect DDI to occur more readily with shorter pulses than with long pulses. This accords with the observations of L'Huillier et al [14] who measured multiphoton ionisation in Xenon using both nanosecond and picosecond pulsed lasers at 1064 nm and 532 nm, and those of Agostini and Petite [15] and Delone et al [16] who measured MPI of Ca at 1064 nm with picosecond pulses and nanosecond pulses respectively. Furthermore, Yergeau et al [17] found that in MPI of rare gases using a CO 2 laser (λ = 9.55µ and 10.55µ), the multiply charged ions are formed sequentially.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Also, for a given power output, the peak intensity in short laser pulses is higher than in longer ones, and hence we should expect DDI to occur more readily with shorter pulses than with long pulses. This accords with the observations of L'Huillier et al [14] who measured multiphoton ionisation in Xenon using both nanosecond and picosecond pulsed lasers at 1064 nm and 532 nm, and those of Agostini and Petite [15] and Delone et al [16] who measured MPI of Ca at 1064 nm with picosecond pulses and nanosecond pulses respectively. Furthermore, Yergeau et al [17] found that in MPI of rare gases using a CO 2 laser (λ = 9.55µ and 10.55µ), the multiply charged ions are formed sequentially.…”
Section: Resultssupporting
confidence: 90%
“…We use equation (9b) for E N (x, x ′ ) and note that the time integration in (14) for the non-local interaction yields the required energy balance E f = E i + 2hω k if and only if we use the retarded interaction ; use of the advanced interaction fails to satisfy energy conservation. (See Appendix B for the mathematical details.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, at 795 nm and a power density of 3.5 ϫ 10 14 W/cm 2 , the presence of a competition between multiphoton ionization (MPI) and Coulomb explosion (CE) channels is revealed by peak shape analysis, and is thought to be operative under these conditions for all of the molecules investigated. T he interaction of intense, ultrafast, laser pulses with atomic [1][2][3][4], small molecular systems [5][6][7][8][9][10][11][12], and polyatomic aromatic organic molecules [13][14][15][16][17][18][19][20][21][22][23], has been the subject of intense investigation. These studies have focused on the fundamental interaction of the laser pulse with the atomic or molecular system, and have generally found a number of operative ionization and dissociation mechanisms present, which are sensitive to the laser wavelength and power density.…”
mentioning
confidence: 99%
“…These two double ionization mechanisms may be identified by their signature imprinted in the kinetic-energy distribution of the ejected protons. Laser-induced non-sequential double ionization of atoms has been extensively studied since its discovery in the early 1980s [1]. This strong field effect as well as highorder harmonic generation (HHG) in rare gases [2] gave birth to the so-called rescattering model which gives a unified picture of the atomic response [3].…”
mentioning
confidence: 99%